Controls on iron(II) fluxes into waterways impacted by acid mine drainage: A Damköhler analysis of groundwater seepage and iron kinetics. (15th April 2019) - Oldham, Carolyn; Beer, Julia; Blodau, Christian; Fleckenstein, Jan; Jones, Lydia; Neumann, Christianne; Peiffer, Stefan
Abstract: When acidic groundwater flows into an aquatic system the sediment water interface (SWI) acts as a transition zone between the groundwater and lake water, and often exhibits strong physical and biogeochemical gradients. The fate of groundwater-borne solutes, such as Fe(II), is determined by the balance between the exposure time during transport across the SWI and the reaction time within the SWI, however the relative role of groundwater seepage rates and iron kinetics on acidity generation in lakes is unknown. Porewater seepage velocities, porewater chemical profiles, and limnological data were collected across multiple field campaigns over the last two decades, in acid Mine Lake 77, in Lusatia, Germany. This rare data set was analyzed using a Damköhler approach that compares exposure and reactions timescales, to determine that Fe(II) would typically be transported with little reaction across the SWI, spatially separating it from sediment-processes that produce alkalinity and providing a source of acidity to the lake. This Damköhler analysis further showed that remediation should be focused on reducing groundwater seepage velocities and enhancing exposure times. Strategic planting of submerged benthic macroalgae would slow groundwater inflows, as well as oxygenating overlying waters and supplying organic matter to the sediments. A similar Damköhler analysis could be used to assess the fate of any groundwater-borne reactive chemicals (e.g. phosphorus) into lakes and streams. Highlights: A Damköhler analysis elucidated the fate of groundwater Fe(II) in a mine lake. Fe(II) was transported across the sediment water interface, providing an acidity source. Benthic macrophytes around groundwater seeps are suggested as remediation options. Damköhler analyses can elucidate the fate of groundwater-borne reactive chemicals.